Quantitative Determination of Surface Markers on B-cell Chronic Lymphocytic Leukemia (CLL) Cells - Niu, Suli (Université d'Ottawa / University of Ottawa, 2014)
To supplement and modify the diagnosis and clinical research of B-cell Chronic Lymphocytic Leukemia (B-CLL), a new method based on cell imaging and image processing was developed and applied to the B-CLL patient samples. The fluorophore-labelled leukemia cells were clearly visualized, reflecting the positive/negative expression of the corresponding surface markers and their distribution. Computer algorithms were devised and used to analyze a large number of images. The fluorescence intensity of the labelled antibodies on a given cell directly reflects the expression of the corresponding surface markers. The morphology and size of leukemia cells were not identical even in the same patient’s sample and the size variation does not correlate with the number of surface markers. The amount of each surface marker was approximately fixed for each patient, but there were some relationships, for instance, the number of CD19 and CD38 markers were correlated to each other. The heterogeneous expression of surface markers confirmed an assumption that surface markers have their preferred membrane positions. One of the most important results is that the cell imaging and our image processing method has provided an alternative and reliable way to diagnose B-CLL and new insights in the prognosis of subtype of B-CLL.
Keywords: B-cell Chronic Lymphocytic Leukemia; CD5; CD19; CD20; CD38; fluorescence microscope; Image J